A comment on fitting Pareto tails to complex survey data - Rafael Wildauer; Jakob Kapeller (Johannes Kepler University Linz, Institute for Comprehensive Analysis of the Economy (ICAE), 2019)
Taking survey data on household wealth as our major example, this short paper discusses some of the issues applied researchers are facing when fitting (type I) Pareto distributions to complex survey data. The major contribution of this paper is twofold: First, we provide a novel take on key aspects of Pareto tail fitting and a new and easy way of implementing the latter. Second, we summarise key results on goodness of fit tests in the context of complex survey data. Taken together we think the paper provides a concise and useful presentation of the fundamentals of Pareto tail fitting with complex survey data.
Keywords: D31; C46; C83; 330; Pareto distribution; complex survey data; wealth distribution